Group I Metabotropic Glutamate Receptor-Mediated Gene Transcription and Implications for Synaptic Plasticity and Diseases - Wang, Hansen; Zhuo, Min (Frontiers in Pharmacology, 2012)
Stimulation of group I metabotropic glutamate receptors (mGluRs) initiates a wide variety of signaling pathways. Group I mGluR activation can regulate gene expression at both translational and transcriptional levels, and induces translation or transcription dependent synaptic plastic changes in neurons. The group I mGluR-mediated translation-dependent neural plasticity has been well reviewed. In this review, we will highlight group I mGluR-induced gene transcription and its role in synaptic plasticity. The signalling pathways (PKA, CaMKs and MAPKs) which have been shown to link group I mGluRs to gene transcription, the relevant transcription factors (CREB and NF-κB) and target proteins (FMRP and ARC) will be documented. The significance and future direction for characterizing group I mGluR-mediated gene transcription in fragile X syndrome, schizophrenia, drug addiction and other neurological disorders will also be discussed.